Possible Approaches to Studying the Influence of Magnetic Fields and Mechanical Effects on the Physicochemical Properties of Aqueous IgG Colloids - Egor I. Nagaev; Elena A. Molkova; Vladimir I. Pustovoy; Tatyana A. Matveeva; Dmitry A. Zakharov; Alexander V. Simakin; Evgenia V. Stepanova; Natalia A. Semenova; Veronika E. Reut; Valery P. Kalinitchenko; Valery A. Kozlov; Nikolai F. Bunkin (Applied Sciences, 2023)
The influence of various mechanical influences (transfusion, stirring, vibration, shaking, etc.) and magnetic installations (used in the application of spin chemistry methods) on colloidal solutions of protein and water, which are often used in pharmaceutical production, was studied. It has been shown that when mechanical influences are applied, physical and chemical properties of water and aqueous colloids of the IgG protein are changed. Magnetic fields do not have a significant effect on water; however, variation in a number of physical and chemical characteristics is observed in protein colloids. Moreover, the effect after exposure to magnetic fields with a frequency of 8 Hz is higher compared to the effect after exposure to magnetic fields with a frequency of 50 Hz. This effect persists even at extremely low concentrations of IgG protein molecules. The measurement system proposed in this work makes it possible to monitor the state of protein molecules in a non-invasive mode. In the future, optical and potentiometric methods built into flow systems can be used at all stages of the production of protein pharmaceuticals.